Determinan yang Mempengaruhi Pengungkapan Laporan Keuangan Pemerintah Daerah - Setyowati, Lilis (Faculty of Economic and Business, 2016)
Determinants That Affect Regional Goverment's Financial Statement DisclosureThis research aims to analysis of factors affecting of financial statement disclosure. The population this study are financial statement of local government all of Indonesia. A total of 314 financial statement of Local Government financial statement 2014 mean of disclosure level is 64%. This result of this study shows that wealth of local government and human development has positive effect on the local government financial statement disclosure, while asset of local government has negative effect. The functional differentiation, debt financing, and intergovernmental revenue are proved to have no effect on the local, government financial statement disclosureDOI: 10.15408/ess.v6i1.3120